Customization of medical report data. - Reiner BI (Journal of Digital Imaging, 2010)
Structured reporting offers a number of theoretical advantages, perhaps the most important of which is creation of standardized report databases. The standardized data created can in turn be used to customize data display, report content, historical data retrieval, interpretation analysis, and results communication in both a context and user-specific manner. In addition, these referenceable report databases can be used to facilitate the practice of evidence based medicine, through data-driven meta-analysis and determination of best practice guidelines. This concept will only be realized if the customized data delivery technology provides real and tangible value to end users, accentuates workflow, can be seamlessly integrated into existing information system technologies, and be shown to yield reproducibility of the evidence domain. The time is here for the medical imaging and clinical communities to embrace this vision in order to improve clinical outcomes and patient safety.